Предмет: Математика,
автор: sergo7054
0,6*(2х+6)=(9-х)*0,6
Ответы
Автор ответа:
1
Ответ:
x=1
Пошаговое объяснение:
1,2x+3,6=5,4x-0,6x
-3,6x=-3,6
×=1
Автор ответа:
0
Ответ:
0,6*(2x+6)=(9-x)*0,6
1,2x+3,6=5,4-0,6x
1,2x+0,6x=5,4-3,6
1,8x=1,8
1,8:1,8
x = 1
Пошаговое объяснение:
0,6*(2*1+6)=(9-1)*0,6
0,6*8=8*0,6
4,8=4,8
Похожие вопросы
Предмет: Английский язык,
автор: Диана277
Предмет: Русский язык,
автор: krist1987
Предмет: Окружающий мир,
автор: vova211106
Предмет: Русский язык,
автор: gdjdjehdjd
Предмет: Английский язык,
автор: nataxa861